Compatibility of Environmentally Friendly Insulating Gases CF3I and c-C4F8 with Cu Contacts - Can Ding; Zhenjiang Gao; Xing Hu; Zhao Yuan (Advances in Condensed Matter Physics)
The gas-solid compatibility between environmentally friendly insulating gas and copper contacts is worth studying. In this paper, based on density functional theory, the adsorption calculation of CF3I, c-C4F8, five typical decomposition gases, and Cu (1 1 1) surface was carried out. The adsorption energies, transferred charges, charge densities, and densities of states were calculated for different adsorption configurations. Research indicates that there is no obvious charge transfer between the I atom and the Cu atom in the four adsorption sites of Cu (1 1 1) for the CF3I molecule. There is a charge transfer between the F atoms and the Cu top surface. The electrons lost by Cu are transferred to F atoms. In the configurations of different adsorption positions on CF3I and Cu (1 1 1) planes, the top and bridge adsorption energies are −0.835 eV and −0.993 eV, respectively, which are chemical adsorption. Therefore, CF3I is most likely to form adsorption at the top or bridge site of the Cu (1 1 1) surface. The adsorption energy of c-C4F8 gas on Cu (1 1 1) surface is similar to that of CF3I at fcc and hcp sites. The absolute values are all less than 0.8 eV, and the van der Waals force is the main force. The adsorption energies of C2F4 and C3F6 in the five decomposed gases are −1.315 eV and −1.204 eV, respectively. The charge transfer is −0.32 eV and −0.45 eV, respectively. Their values are larger than those of the other gases studied, which belong to chemical adsorption. The smaller values of the remaining three gases belong to physical adsorption. All molecular structures and Cu (1 1 1) planes were not significantly deformed. From a microscopic point of view, the gas can better exist on the copper surface.